2010
DOI: 10.2320/matertrans.m2009438
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Properties of Cold-Rolled Ni<SUB>3</SUB>(Si,Ti) Intermetallic Foils for Methanol Decomposition

Abstract: Methanol decomposition tests were carried out for the first time on cold-rolled Ni 3 (Si,Ti) foils in a temperature range of 513-793 K to investigate their potential catalytic properties for hydrogen production. The catalytic activity was observed at temperatures above 713 K. At 793 K, the catalytic activity changed with the reaction time in three stages: low-activity incubation, rapid spontaneous activation and highactivity state. Surface analysis revealed an intensive formation of fine Ni particles on the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Furthermore, the H 2 production rate at ≤400 °C was greater during cooling than during heating. Studies reported that Ni 3 Al and Ni 3 (Si,Ti) form Ni fine particles on the surface because of the selective oxidation of Al and Si, respectively, during methanol decomposition, thereby exhibiting high activity. Similarly, after SRM, Ni 2 TiAl exhibited Ni fine particles, as can be observed by X-ray diffraction (XRD) and scanning electron microscopy (SEM) analyses (Figure a,b, respectively); these fine particles were probably formed because of the selective oxidation of Ti as revealed by X-ray photoelectron spectroscopy (XPS) analysis summarized in Table . The increased H 2 production rate at ≥450 °C and the higher H 2 production rate at 400 °C during cooling than during heating were attributed to the Ni fine particle formation.…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, the H 2 production rate at ≤400 °C was greater during cooling than during heating. Studies reported that Ni 3 Al and Ni 3 (Si,Ti) form Ni fine particles on the surface because of the selective oxidation of Al and Si, respectively, during methanol decomposition, thereby exhibiting high activity. Similarly, after SRM, Ni 2 TiAl exhibited Ni fine particles, as can be observed by X-ray diffraction (XRD) and scanning electron microscopy (SEM) analyses (Figure a,b, respectively); these fine particles were probably formed because of the selective oxidation of Ti as revealed by X-ray photoelectron spectroscopy (XPS) analysis summarized in Table . The increased H 2 production rate at ≥450 °C and the higher H 2 production rate at 400 °C during cooling than during heating were attributed to the Ni fine particle formation.…”
Section: Resultsmentioning
confidence: 90%